2018
DOI: 10.1128/aem.02168-17
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics Reveals the Impact of Wastewater Treatment Plants on the Dispersal of Microorganisms and Genes in Aquatic Sediments

Abstract: Wastewater treatment plants (WWTPs) release treated effluent containing mobile genetic elements (MGEs), antibiotic resistance genes (ARGs), and microorganisms into the environment, yet little is known about their influence on nearby microbial communities and the retention of these factors in receiving water bodies. Our research aimed to characterize the genes and organisms from two different WWTPs that discharge into Lake Michigan, as well as from surrounding lake sediments to determine the dispersal and fate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 45 publications
9
111
4
Order By: Relevance
“…On the other hand, the bacterial Moraxellaceae sp. was found in the broad range of sources, such as wastewater treatment plant sludge, lake sediment [16], activated sludge in a continuous up-flow reactor [17], and sea water [18], whereas the cyanobacteria Kamptonema sp. were found spread in wet soil, plant bark, and stream sand [19].…”
Section: Microbial Communitymentioning
confidence: 99%
“…On the other hand, the bacterial Moraxellaceae sp. was found in the broad range of sources, such as wastewater treatment plant sludge, lake sediment [16], activated sludge in a continuous up-flow reactor [17], and sea water [18], whereas the cyanobacteria Kamptonema sp. were found spread in wet soil, plant bark, and stream sand [19].…”
Section: Microbial Communitymentioning
confidence: 99%
“…Wastewater and wastewater treatment plants (WWTPs) contain a variety of antibiotic resistance genes (ARGs) that can be transmitted into the environment through the discharge of effluents (Szczepanowski et al, 2009;Berendonk et al, 2015;Chu et al, 2018;Petrovich et al, 2018). Hospital wastewater is thought to be a particularly important driver of selection for ARGs in WWTPs because it often contains antibiotic resistant bacteria and antibiotic residues at higher concentrations than other urban wastewater sources (Baquero et al, 2008;Rodriguez-Mozaz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The taxonomy-resolved structure of the environmental resistome has mostly been evaluated in culture-based studies, which are able to assess resistance phenotypes and genetic determinants of isolates [14,20]. Recently, several studies have demonstrated host-tracking of the environmental resistome based on the taxonomic classification of metagenomic contigs harboring ARGs [31]. Although metagenomics approaches have advantages over culturedependent approaches in terms of elucidating comprehensive and unbiased resistome profiles, especially for complex environmental communities, they are limited in terms of providing accurate taxonomic information and solid phenotypic evidence.…”
Section: Discussionmentioning
confidence: 99%